Effect of the centrifugal and centripetal forces in core versus (semi)periphery in Central Europe countries - Martin Maris (European Regional Science Association (ERSA), 2015)
Evolution of the regional imbalances over the territory is closely linked with the development of commodity-cash relations and hence with creation of the market economy. Since the establishment of the market economy in most countries over the world; rent, interest, yield and wage became the major market driver of the production factors in order to make its localization decisions. It led to spatial organization and deployment of the scarce resources over the territory. The specific feature of these scarce resources is, that they are distributed unevenly over the territory. In the background affects centrifugal and centripetal forces which condition the concentration of the scarce resources in some areas and conversely its deconcentration in other areas. Main object of the paper is to analyse and evaluate effects of centrifugal and centripetal forces on regional economies of the Central Europe countries and recognize some common spatial patterns of the development. In our empirical research we focus on the Central Europe countries, namely Czech Republic, Austria, Slovakia and Hungary. Our sample consists regions of these countries on NUTS III level. For analysis of spatial imbalance within the territory of CE countries we use state variable - regional GDP / capita. In terms of examining causal relations of regional disparities in CE countries is appropriate to rely on tools of spatial statistical analysis. From this point we are concerned with measuring the spatial relations within the regional structure of CE countries. Preliminary we suppose that strongest influence of the centrifugal and centripetal forces is present around the core regions of CE countries, namely: Praha, Bratislava, Wien and Budapest. The object of our paper is measuring the intensity of these forces. Primarily, we examine the spatial imbalance within regions of the CE countries via using the Morans autocorrelation statistics, I (1950). We suppose that the spatial differentiation within the regions of CE countries acquire more or less regular pattern, so it, indicates that regional imbalance is conditioned also spatially. Secondary, in more details we focus on local patterns in spatial-temporal data on the wealth, centering on our core regions. For these purpose we use the statistics G_i (d) introduced by Getis and Ord (1992). Our research is based on secondary data sources collected in statistical databases of CE countries . As a basis for measurement we took indicator of regional GDP / capita converted to dollars at PPP. We expect to show on the effects of centrifugal and centripetal forces, which creates clear clusters around the core regions. It also supposes that some signs of the spatial imbalances over the territory are also presents. In conclusion we have to examine possible factors which condition present state.
Keywords: R12; 330; region; centrifugal and centripetal forces; spatial imbalance; spatial autocorre